Validación de los estrato de cobertura vegetal en la concesión para conservación el breo (CCEB) - Sánchez Céspedes, Willy William (2013)
The present study aims, to validate the strata of vegetation in the Conservation Concession "The Breo" (CCEB), Huicungo 2012, taking into account the importance that involves determining the type of vegetation cover and area studies could be made in it. As the inventory of existing flora has been made 2 entrances to the area of the concession for Conservation The breo identified 141 species in 51 families and 33 orders, showing a dominance the Family Rubiaceae with 1 O species, this was a reference in the classification generated. In the cabinet stage was identifying and working satellite images LANDSAT 5 of 1999, 2001 and 2008 to identify the NDVI index; ASTER GDEM for the identification of the shape ofthe earth and the images ofWorldclim for Temperature and Precipitation, used for analyzing images in ArcGIS 10.1 software. Validated classification was determined by crossing data and layers, resulting in six classifications, which will support the conservation and management studies conducted in the study area. This paper presents a contribution to the spatial distribution of vegetation strata of the Concession Area for Conservation The Breo. Key words: study